Evaluation of human resources capacity, institutional and marketing in the Minapolitan Area, Merangin Regency, Jambi Province - Suprianto, Dedi; Effendi, Irzal; Budiardi, Tatag; Widanarni, Widanarni; Diatin, Iis; Hadiroseyani, Yani (Universitas Malikussaleh, 2023)
Evaluation of human resource development and institutional aspects is a process of providing information that can be used as a consideration to improve capabilities and be able to influence the implementation of community empowerment programs. The aimed of this study was to evaluate the capacity of human resources, institutions, and aquaculture marketing systems in the minapolitan area of Merangin Regency. The method of data collection was carried out using a structured interview method with the help of a questionnaire to 493 fish cultivating households (CH). Data were analyzed by multidimensional scaling and leverage analysis using Rapfish software. The results showed that the CH of catfish obtained the highest average index of 55.58, followed by the CH of gouramy at 53.60, the CH of tilapia at 54.57 and the CH of catfish obtained an average index of 54.71. This illustrates that the performance of catfish farmers in aquaculture production technology and management systems is better than the performance of other fish farmers. The results of the evaluation of all aspects of the capacity of human resources, institutions, and aquaculture marketing systems indicate that there are 3 aspects that are in the range of 50.10-75.00 with moderately sustainable status, namely; human resource development aspect with an average index value (AIV) of 68.64, technology aspect with an AIV of 52.98, and natural resources aspect with an AIV of 65.22. Meanwhile, there are 2 aspects that are in the range of 25.10-50.00 with less sustainable status, namely the institutional aspect with an AIV of 48.23 and the economic aspect with an AIV of 48.62.Keywords: Aquaculture; Institutional; Marketing; Sustainability